PROBLEMS OF DIGITALIZATION OF THE RUSSIAN INDUSTRY - Y. S. Bogachev; P. V. Trifonov; N. M. Abdikeev (Стратегические решения и риск-менеджмент, 2022)
The article is devoted to the substantiation of the model of the formation of an industrial development ecosystem based on modern digital technologies in industry.The article deals with the problems of technological sovereignty of the Russian economy. It is shown that the solution of this problem is possible only on the basis of an industrial development ecosystem – a system of production chains of the most important types of industrial products, a technological development platform, interaction of subjects of industrial production with consumers of its products in the domestic and foreign markets. The necessity of concentration of industrial potential, resources of technological development, qualified personnel potential and direction to create conditions for providing the Russian economy with products corresponding to the world technological level is shown. The article analyzes the main existing and promising models of the functioning of an industrial enterprise. A detailed description of the barriers and difficulties on the way of digitalization of industrial enterprises in the Russian Federation is given.In order to form the ecosystem of industrial development of the Russian Federation, the directions of identifying and assessing the state of production and technological personnel potential, its compliance with the needs of the domestic market are formulated. Recommendations are given on the creation of an ecosystem structure, mechanisms for the interaction of its various elements, a management and coordination system based on digital technologies for creating a system of individual elements that form information and analytical centers in various functional areas of the ecosystem.A model of the ecosystem of industrial and technological development of the Russian economy based on digital technologies is proposed.A set of mechanisms that contribute to reducing the level of uncertainty is proposed, and a design method of interaction within the framework of the digital industrial enterprise technology platform model is described.The article formulates recommendations for the digitalization of an industrial enterprise in the new technological conditions of economic and social development, in the so-called new technological paradigm “Industry 4.0”, the characteristic features of which are minimal use of manual and mechanized labor, as well as a low level of transaction costs.A new approach is proposed, on the basis of which industrial enterprises will interact on the basis of shared access to information and digital resources and the ability to combine the development of innovative projects and value chains necessary to create competitive products in order to increase the operational efficiency of enterprises.